Tracheobronchial Foreign Bodies in Children: Experience From 1,328 Patients in China - Ding, Ling; Su, Shuping; Chen, Cheng; Yao, Hongbing; Xiao, Ling (Frontiers in Pediatrics, 2022)
Objective: To analyze the clinical characteristics of tracheobronchial foreign body (FB) cases in a pediatric Chinese population. Methods: The clinical data of pediatric patients aged 0–14 years old diagnosed with a tracheobronchial FB in the Children’s Hospital of Chongqing Medical University between September 2018 and August 2021 were analyzed retrospectively. Results: Among 1328 included cases, 92.09% of patients were less than 3 years old, and the peak incidence of tracheobronchial FB occurred in patients 1–2 years old. The male to female ratio was 1.86:1, and the prevalence of tracheobronchial FB was similar between patients living in rural and urban areas. The most common presenting symptoms were cough and wheezing, followed by fever and dyspnea. The most common FB type was nuts (81.17%). FBs were more frequently located in the right bronchus, and 64 (4.82%) cases involved multiple FBs. At least one complication occurred in 90.36% of cases, and complications were less frequent in tracheal FB cases than in cases of bronchial and multiple FBs (P<0.05). FBs were expelled by coughing in only 4.07% of cases. For the other cases, FB removal by first bronchoscopy was successful and complete in 96.86% of cases. The 11.3% of cases that did not report FB aspiration on admission had a longer time to hospital admission, longer hospitalization time, and higher rate of complications than cases reporting FB aspiration (P<0.05). Conclusions: Tracheobronchial FBs occurred most commonly in children less than 3 years old, and rigid bronchoscopy remains the first-line method for FB removal in children.